Minimizing environmental impact whilst securing drinking water quantity and quality demands from a reservoir. (15th March 2019) - Weber, Michael; Boehrer, Bertram; Rinke, Karsten
Abstract: Complying with the demands of drinking water supply whilst minimizing environmental impact poses a great challenge in water management. This study investigates the potential of withdrawal management of drinking water reservoirs to alleviate the disruption of the river continuum by a reservoir dam with respect to temperature and discharge. The aim is the identification of an optimal withdrawal strategy to provide a near‐natural discharge temperature and flow for the downstream river without jeopardizing drinking water production. First, we identify the applicability of new withdrawal regimes for raw water security and downstream river demands. Second, we search for an ideal withdrawal regime in scenario simulations using a numerical reservoir model ("General Lake Model"). The scenarios on a drinking water reservoir in Germany demonstrate that we are able to derive an optimized reservoir management. The numerical model is provided for operators as a simple and efficient tool for optimizing the withdrawal strategy within reservoir management.